Forward Genetic Analysis of the Circadian Clock Separates the Multiple Functions of ZEITLUPE - Kevei, Éva (American Society of Plant Biologists, 2006)
The circadian system of Arabidopsis (Arabidopsis thaliana) includes feedback loops of gene regulation that generate 24-h oscillations. Components of these loops remain to be identified; none of the known components is completely understood, including ZEITLUPE (ZTL), a gene implicated in regulated protein degradation. ztl mutations affect both circadian and developmental responses to red light, possibly through ZTL interaction with PHYTOCHROME B (PHYB). We conducted a large-scale genetic screen that identified additional clock-affecting loci. Other mutants recovered include 11 new ztl alleles encompassing mutations in each of the ZTL protein domains. Each mutation lengthened the circadian period, even in dark-grown seedlings entrained to temperature cycles. A mutation of the LIGHT, OXYGEN, VOLTAGE (LOV)/Period-ARNT-Sim (PAS) domain was unique in retaining wild-type responses to red light both for the circadian period and for control of hypocotyl elongation. This uncoupling of ztl phenotypes indicates that interactions of ZTL protein with multiple factors must be disrupted to generate the full ztl mutant phenotype. Protein interaction assays showed that the ztl mutant phenotypes were not fully explained by impaired interactions with previously described partner proteins Arabidopsis S-phase kinase-related protein 1, TIMING OF CAB EXPRESSION 1, and PHYB. Interaction with PHYB was unaffected by mutation of any ZTL domain. Mutation of the kelch repeat domain affected protein binding at both the LOV/PAS and the F-box domains, indicating that interaction among ZTL domains leads to the strong phenotypes of kelch mutations. Forward genetics continues to provide insight regarding both known and newly discovered components of the circadian system, although current approaches have saturated mutations at some loci.